Comparação entre os valores de pressão intraocular aferidos por tonômetros de aplanação (Tono-Pen AVIA®) ede rebote (Tonovet Plus®) e determinação dos valores dereferência para a pressão intraocular e Teste lacrimal de Schirmer em coelhos Mini Lion Head hígidos - Viega, Ismael de Oliveira (2023)
Intraocular pressure (IOP) and tear production rate are essential parameters that must be evaluated during the ophthalmological examination. The Schirmer tear test and tonometry are the tests that measure the production of the precorneal tear film (CPFL) and IOP, respectively. IOP may be altered in ocular or systemic diseases that cause pressure changes and may impair vision, such as glaucoma and uveitis. FLPC plays a key role in maintaining the health of the ocular surface and its inadequate production can lead to harmful changes to the cornea and conjunctiva. Research with various models and brands of available tonometers showed statistically significant differences in IOP values in different animal species. In the veterinary literature, both ophthalmic parameters (IOP and tear production) still do not have reference values for some animal species. This work aimedto define the normal values of tear production and IOP in pet Mini Lionhead rabbits (Oryctolagus cuniculus), as well as to compare the IOP obtained with the rebound tonometer model TonoVet Plus® and with the applanation tonometer model Tono-Pen Avia® 25 rabbits (50 eyes) from theProductive Didactic Module of Rabbit Breeding at the Center for Agricultural Sciences (CCA) at UFPB. Tear production was measured at 6:00 am and 6:00 pm with standardized strips of absorbent paper (Schirmer's test). The IOP reading was performed first with the rebound tonometer and then with the applanation tonometer, both performed by the same examiner, in five moments of the same day (6:00 am, 9:00 am, 12:00 pm, 3:00 pm and 6:00 pm), in order to observe circadian changes in the parameter. Statistical analyzes used were regression analysis, analysis of variance (ANOVA) and Bland-Altman.Mean tear production was 10.25 ± 3.75 mm/min, with no statistical difference between the evaluated moments. The average daily IOP was17.7 ± 3.08 mmHgwith the TonoVet Plus® tonometer and11.5 ± 4.56 mmHgwith the Tono-Pen Avia® tonometer, and the IOP values were significantly higher (about 6.1 mmHg) with the TonoVet Plus®.Mean IOP values were significantly higher at the beginning and end of the day with both tonometers. The normal reference values of tear production and IOP obtained in this study, as well as the reference data for the use of two tonometers, one for applantion and the other for rebound, may support the diagnosis, treatment and adequate monitoring of ocular disorders in Pet Mini Lionhead rabbits.